Estrategias publicitarias para el comercial Minimarket Anthony del cantón Babahoyo - Espinoza Gonzabay, Carmen Elena (2021)
The Minimarket Anthony S.A commercial was created on September 12, 2006, it has its headquarters and several branches, but the main one is located on the university avenue in front of the Eugenio Espejo School, within the city of Babahoyo, Los Ríos province. In addition to the Matrix, it has branches inside and outside the province of the rivers where more branches have been added nationwide. This company is affected by competition, which is the big problem in sales, the inappropriate commercialization of mass consumer products due to the little use of processes carried out in the commercial, within its business. Marketing strategies are traditional views as advances in computing, communication and information technology forever changed the world and the ways companies reach potential customers, the customer or consumer is the most important asset of the company because all efforts are directed to meet your needs. According to the surveys carried out in the Babahoyo canton, it is concluded that the Commercial "Minimarket Anthony" should take into account as a point to apply the publications and promotion of new products for their commercialization, since the people who acquire the products are focusing on the traditional and how they are promoted.